Comparison Between State and Private University Student of Adversity Quotient on Online Learning - Mardiana, Dina; Umiarso, Umiarso (Journal of Education and Computer Applications, 2025)
This study intends to investigate how Adversity Quotient (AQ) or Intelligence in Facing Student Obstacles might be formed through online learning at PTKIs, the Private University in Malang and the Universitas Muhammadiyah Malang. The COVID-19 epidemic, which compelled universities to adapt to online learning, caused alterations in learning patterns at PTKI, which served as the foundation for this study. The study aimed to explore the Adversity Quotient among students, focusing on four core dimensions: Control, Ownership, Reach, and Endurance. Additionally, the study examined four dimensions pertinent to online learning: Student Performance, Technology, Lecturer, and Self-Regulation. As a result, it is clear that the responders at the State University of Malang have performed admirably, are able to overcome obstacles, and are able to maximize the potential that rises daily. In contrast to the low scores of University "X" Malang respondents. As long as life proceeds pretty smoothly, the individual is often responsible for navigating it. However, the individual may experience more setbacks or become disheartened by the accumulation of life's difficulties In addition to offering recommendations for the future development of online learning, it is envisaged that this research will give an overview of how online learning at PTKI can affect students' AQ.